Learning DNS understanding domain name servers and resource records - Liu, Cricket (Infinite Skills, 2015)
"In this Learning DNS training course, expert author Cricket Liu will teach you about the theory behind the Domain Name System. This course is designed for the absolute beginner, meaning no prior knowledge of DNS is required. You will start by learning how DNS works, including learning about resolvers, resolution and recursion, and caching. From there, Cricket will teach you about name servers, such as authoritative, primary, secondary, and forwarders. This video tutorial also covers common types of resource records, including the A record, MX record, and wildcards. Finally, you will learn about DNS query tools including nslookup and dig, as well as advanced topics such as NOTIFY and sender policy framework. Once you have completed this computer based training course, you will have gained a solid understanding of Domain Name Servers and resource records."--Resource description page.
Title taken from title screen (viewed July 29, 2015). - Date of publication taken from resource description page
Keywords: Internet domain names; Internet addresses; Adresses Internet